Review of Monstrous Textualities: Writing the Other in Gothic Narratives of Resistance - Osoliová, Viktória (AMERICANA E-journal of American Studies in Hungary, 2021)
Monstrous Textualities: Writing the Other in Gothic Narratives of Resistance Anya Heise-von der Lippe Wales: University of Wales Press, 2021 329 pages ISBN 978-1-78683-758-5